Health Concern of Phenomenally Premium Boba Milk Tea and Pearls Beverages in Kuala Lumpur: Sugary Content and Physico-chemical Profiles Analysis - Saiful Irwan Zubairi; Zalifah Mohd Kasim; Muhammad Harith Afifi Muhamad Zahiri; Nur Huda Faujan (Enviro Research Publishers, 2024)
Indexed by WOS/ Scopus